University and Sustainable Urban Development Indicators for Analysis and Evaluation1 - Romero, Gemma Durán; Laguna Molina, Nuria E. (European Journal of Sustainable Development, 2017)
University is an institution with a high potential to promote changes that lead to better social outcomes in terms of sustainability and social responsibility. Therefore, it is seems highly necessary to know what sustainability strategies Universities are following, to what extent they are assuming their role as agents of change and in what lines of work they should deepen in order to achieve the Sustainable Development Goals. The objective of this paper is to present the results of a research work that analyses and evaluates, from an interdisciplinary approach, the role of universities in sustainable development. More specifically, the paper carries out an evaluation of the strategies adopted by three Spanish universities: Universidad Auto?noma de Madrid, Universidad Carlos III of Madrid and Universidad de Castilla-La Mancha. The final output of this work is a system of University Sustainability Assessment Indicators, which will allow, on the one hand, monitoring of university actions in sustainability and, on the other, formulate new initiatives that improve university sustainability performance.